2000
DOI: 10.1021/la9909190
|View full text |Cite
|
Sign up to set email alerts
|

Phase Diagram and Phase Properties of the System Lecithin−Water−Cyclohexane

Abstract: The isothermal quasi-ternary-phase diagram of the lecithin-cyclohexane-water system was determined at 25 °C using a combination of polarizing microscopy, small-angle X-ray diffraction, and NMR techniques. The system contains four lyotropic liquid-crystalline phases and two isotropic liquid phases. Apart from the lamellar (LR) phase, there are only reverse-type aggregates with a water interior, in addition to an essentially pure water phase, whose relative locations in the phase diagram follow the sequence (fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
104
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 30 publications
9
104
2
Order By: Relevance
“…Next, in Figure 6, we compare these dimensions with those of lecithin reverse micelles measured by Schurtenberger et al using SANS 9 and with those of lecithin inverse hexagonal phase measured by Angelico et al using SAXS. 6 We argue the comparison of the structure of simulated DSPC RMs to the structural trends of lecithin RMs at a lower temperature is justified because the viscosity behavior of all PC/cyclohexane organogels is very similar despite significant differences in temperature and fatty acid tail composition. Figure 6 shows the cross-sectional radius of lecithin RMs increases between water ratios 6-14 experimentally and this trend is visible also in the radii calculated from the simulated RMs.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Next, in Figure 6, we compare these dimensions with those of lecithin reverse micelles measured by Schurtenberger et al using SANS 9 and with those of lecithin inverse hexagonal phase measured by Angelico et al using SAXS. 6 We argue the comparison of the structure of simulated DSPC RMs to the structural trends of lecithin RMs at a lower temperature is justified because the viscosity behavior of all PC/cyclohexane organogels is very similar despite significant differences in temperature and fatty acid tail composition. Figure 6 shows the cross-sectional radius of lecithin RMs increases between water ratios 6-14 experimentally and this trend is visible also in the radii calculated from the simulated RMs.…”
Section: Resultsmentioning
confidence: 96%
“…5 Maximum water uptake in cyclohexane is around w 0 = 24; at higher water-tolipid ratios the system phase separates into a microemulsion phase and an excess water phase. 5 The organogel transition and the viscous characteristics of the solution, as well as, the size change in the amphiphilic aggregates can be characterized experimentally very well with, e.g., rheological measurements, 10 NMR self-diffusion, 5 and scattering techniques including light, 8 neutron, 7,9 and X-ray 6 scattering. This provides experimental comparison data for simulations at the level of basic structural characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, calculations based on molar volumes of PC and CL apolar tails (0.634 l/mol, Angelico et al 2000)) showed that the fraction of hydrophobic phase available for UQ-10 and herbicide molecules in liposomes, should be around 2 × 10 -3 , thus increasing their effective availability towards the RCs by ∼2000 times compared to their analytical nominal concentration in the sample. In this view, the topological discontinuity of the bilayer hydrophobic domain compared to the continuous aqueous phase (similarly to the discontinuity of the hydrophobic domain of the RC-DDAO micelles (Shinkarev and Wraight 1997)) accounts for the significant role in the ubiquinone distribution in proteoliposomes .…”
Section: Discussionmentioning
confidence: 99%
“…These reverse worms become tangled in the oil and form a three-dimensional (3D) network throughout the solution, turning the solution into an gel-like solution (also called a lecithin organogel). [1][2][3][4][5][6] In this reverse micellar system the polar substance is the key ingredient for the formation of reverse worms. We have also identified other key ingredients that can be used as substitutes for water in the preparation of reverse worms in n-decane, such as urea, 7) sucrose fatty acid esters, 8) D-ribose, 9) 2-deoxy-D-ribose, 9) polyglycerols, 10) ascorbic acid, 11) and multivalent carboxylic acids.…”
mentioning
confidence: 99%